The non-linear optical crystal growth and characterization of piperizantum p- aminobentzone - Vallikkodi, M; Sudhahar, S (BIBECHANA, 2018)
The nonlinear optical properties of piperizanium p – aminobenzoate (PZPAB) crystal were successfully grown with the help of temperature gradient (Slow evaporation) method. The good quality of PZPAB single crystal is formed. The PZPAB is characterized with the help of X-ray diffraction (XRD), Fourier transform infrared (FTIR) measurement, photoluminescence (PL), Raman spectroscopy, ultra violet visible spectroscopy (UV) and finally etching analysis was done. BIBECHANA 6 (2019) 5-22